Beliefs towards the COVID-19 pandemic among patients with emotional disorders in China. Issue 3 (9th June 2020) - Gao, Yining; Sun, Fei; Jiang, Wenwen; Fang, Yuan; Yue, Ling; Lin, Xiang; Li, Xia
Abstract : Background: The novel coronavirus disease 2019 (COVID-19) pandemic has given rise to fear and panic in the public. Although hospitals in China reduced outpatient visits and restricted inpatient admission to lower the risk of transmission of COVID-19, this has significantly affected patients in need of medical attention, for example, patients with emotional disorders. Aims: This study aimed to compare the beliefs towards COVID-19 among outpatients with emotional disorders (ie, anxiety or depression) with those of family caregivers and the general public and examine factors that shape the beliefs towards COVID-19 among outpatients with emotional disorders. Methods: Survey data from 570 outpatients with anxiety or depression disorders, 449 family caregivers and 470 general public subjects were collected. Multiple stepwise regression analyses were used to describe participants' level of concern, prevention attitude and positive expectations towards the COVID-19 outbreak. Results: About 70.9% of outpatients had to postpone their mental health treatment; 43.2% of patients admitted that their mental health was adversely affected by the COVID-19 outbreak—these patients tended to be older, male and less educated. After controlling for age and education level, outpatients with emotional disorders had significantly lower levels of concerns but more negative expectations towards COVID-19, compared with family caregivers and the public. Multivariate linear stepwise regression analysis showed that age, education and the perception of the impact of COVID-19 on one's existing mental illness were significantly associated with outpatients' beliefs about the epidemic. Conclusion: Outpatients with anxiety or depression disorders were relatively less focused on the COVID-19 outbreak, but the impact of the infection was found to be independently associated with their beliefs towards COVID-19. In addition, outpatients who were older and of low educational levels particularly held more negative beliefs about the epidemic, which may place them at a higher risk for poor mental health.